Biocompatibility and osseointegration properties of a novel high strength and low modulus β- Ti10Mo6Zr4Sn3Nb alloy - Liu, Jiantao; Wang, Kao; Li, Xingyuan; Zhang, Xiwei; Gong, Xi; Zhu, Yihan; Ren, Zhiwei; Zhang, Bin; Cheng, Jun (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Ti6Al4V titanium alloy is widely used in producing orthopedic and maxillofacial implants, but drawbacks include high elastic modulus, poor osseointegration performance, and toxic elements. A new medical titanium alloy material with better comprehensive performance is urgently needed in the clinic. Methods: Ti10Mo6Zr4Sn3Nb titanium alloy (referred to as Ti-B12) is a unique medical ß titanium alloy material developed by us. The mechanical properties of Ti-B12 depict that it has advantages, such as high strength, low elastic modulus, and fatigue resistance. In our study, the biocompatibility and osseointegration properties of Ti-B12 titanium alloy are further studied to provide theoretical guidance for its clinical transformation. Results and Discussion: The titanium alloy Ti-B12 displays no significant effect on MC3T3-E1 cell morphology, proliferation, or apoptosis in vitro. Neither Ti-B12 titanium alloy nor Ti6Al4V titanium alloy depicts a significant difference (p > 0.05); Ti-B12 material extract injected into the abdominal cavity of mice does not cause acute systemic toxicity. The skin irritation test and intradermal irritation test reveal that Ti-B12 does not cause skin allergic reactions in rabbits. Compared to Ti6Al4V, Ti-B12 titanium alloy material has more advantages in promoting osteoblast adhesion and ALP secretion (p < 0.05). Although there is no significant difference in OCN and Runx2 gene expression between the three groups on the 7th and 14th days of differentiation induction (p > 0.05), the expression of Ti-B12 group is higher than that of Ti6Al4V group and blank control group. Furthermore, the rabbit in vivo test present that 3 months after the material is implanted in the lateral epicondyle of the rabbit femur, the Ti-B12 material fuses with the surrounding bone without connective tissue wrapping. This study confirms that the new β-titanium alloy Ti-B12 not only has low toxicity and does not cause rejection reaction but also has better osseointegration performance than the traditional titanium alloy Ti6Al4V. Therefore, Ti-B12 material is expected to be further promoted in clinical practice.